2022
DOI: 10.1038/s41467-022-28452-z
|View full text |Cite
|
Sign up to set email alerts
|

Copy number amplification of ENSA promotes the progression of triple-negative breast cancer via cholesterol biosynthesis

Abstract: Copy number alterations (CNAs) are pivotal genetic events in triple-negative breast cancer (TNBC). Here, our integrated copy number and transcriptome analysis of 302 TNBC patients reveals that gene alpha-endosulfine (ENSA) exhibits recurrent amplification at the 1q21.3 region and is highly expressed in TNBC. ENSA promotes tumor growth and indicates poor patient survival in TNBC. Mechanistically, we identify ENSA as an essential regulator of cholesterol biosynthesis in TNBC that upregulates the expression of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…This patient progressed within 7 months on trastuzumab, emphasising the need for regular re-evaluating tumour characteristics during the course of the disease, as is shown possible with liquid biopsies. Moreover, various additional amplifications were seen in 1q, 5q, 12, and 16p, in part of the CTC and DTC samples of patient 3, stressing the aggressive nature, possibly even subtype switch, of the metastatic disease in this patient that was ER+ on primary tumour biopsy (51), as chromosome 1q and 12p amplifications are associated with TNBC/basal-like breast cancer and poor survival (54,55). These co-occurring alterations, absent in the primary tumour, were initially predominantly present in the bone marrow, then emerging in the cerebrospinal fluid, to only become dominant in the CTC compartment after second progression.…”
Section: Discussionmentioning
confidence: 91%
“…This patient progressed within 7 months on trastuzumab, emphasising the need for regular re-evaluating tumour characteristics during the course of the disease, as is shown possible with liquid biopsies. Moreover, various additional amplifications were seen in 1q, 5q, 12, and 16p, in part of the CTC and DTC samples of patient 3, stressing the aggressive nature, possibly even subtype switch, of the metastatic disease in this patient that was ER+ on primary tumour biopsy (51), as chromosome 1q and 12p amplifications are associated with TNBC/basal-like breast cancer and poor survival (54,55). These co-occurring alterations, absent in the primary tumour, were initially predominantly present in the bone marrow, then emerging in the cerebrospinal fluid, to only become dominant in the CTC compartment after second progression.…”
Section: Discussionmentioning
confidence: 91%
“…(Figure 4f). The abnormal cholesterol metabolism is reported to be closely related to the occurrence of a wide variety of tumor development (Chen et al., 2022). And a number of clinical and preclinical studies demonstrated that intervening the cholesterol metabolism in tumor cells and immune cells has been proved to be an effective treatment against cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Since somatic copy number alteration (SCNA) detection tools are prone to high false positive rates as well as issues with precision and accuracy ( 59 , 60 ), we also performed SCNA calling using CNVkit ( 61 ), which combines all normal samples into a pooled reference to increase performance. In contrast to Sequenza, this method identified a greater number of SCNA in primary TNBC relative to BrM, showing that, as a collective group, primary TNBC samples harbored 27 significant amplicons and 17 deleted regions, whereas BrM had 8 significant amplicons and 4 regions of deletion ( q < 0.25; Figures 1E, F ) .…”
Section: Resultsmentioning
confidence: 99%